2005
DOI: 10.1002/ejic.200500415
|View full text |Cite
|
Sign up to set email alerts
|

An Approach Towards Functional Dendrimers Based on the Hydroboration Reaction and Spontaneous Boron–Nitrogen Bond Formation

Abstract: The reaction of 1,4‐bis‐ or 1,3,5‐tris(bromoboryl)benzenes 4 and 6, respectively, with 2 or 3 equiv. of 4,4′‐bis(but‐3′′‐enyl)‐2,2′‐bipyridyl (2) leads to the corresponding 2,2′‐bipyridylboronium cations 5 and 7 in almost quantitative yield. Using the monocation [(MeC6H4)B(Br){4,4′‐bis(but‐3′′‐enyl)‐2,2′‐bipyridyl}]+ (3Br) as a model system, it is shown that the olefinic side‐chains of such compounds are readily transformed into alkyldibromoborane functionalities by hydroboration with HBBr2. Subsequent additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 25 publications
(26 reference statements)
0
4
0
1
Order By: Relevance
“…of BBr 3 and heated and then dried in-vacuo) showed a gradual change in the 11 B NMR spectra whereby the boron centre in the cationic component was shifted gradually downfield from δ 11B = 37.5 to δ 11B ca. 42 ppm (in the range expected for an ArylB(OR)Br species), [19] whereas the second resonance was shifted upfield from δ 11B = À 16.6 to δ 11B = À 25 ppm (Figure 6), the latter is as expected for a discrete BBr 4 À anion. Thus, it can be concluded that upon cooling of the sample, the product favours the salt form, 8 A.…”
Section: Resultsmentioning
confidence: 61%
“…of BBr 3 and heated and then dried in-vacuo) showed a gradual change in the 11 B NMR spectra whereby the boron centre in the cationic component was shifted gradually downfield from δ 11B = 37.5 to δ 11B ca. 42 ppm (in the range expected for an ArylB(OR)Br species), [19] whereas the second resonance was shifted upfield from δ 11B = À 16.6 to δ 11B = À 25 ppm (Figure 6), the latter is as expected for a discrete BBr 4 À anion. Thus, it can be concluded that upon cooling of the sample, the product favours the salt form, 8 A.…”
Section: Resultsmentioning
confidence: 61%
“…The δ 11B = 40.4 is consistent with boron in an ArB(OR)Br environment. 18 Finally, it should be noted that leaving mixtures containing 3 for longer reaction times led to the conversion of 3 into 2a , suggesting 3 is an intermediate in the production of 2a .…”
Section: Resultsmentioning
confidence: 98%
“…However, the identity of 3 is supported by comparison to Me 3 N/BHBr 2 which displays a d 11B = −0.7 doublet with an identical 1 J B-H coupling constant (156 Hz) to that observed in 3. 17 18 Finally, it should be noted that leaving mixtures containing 3 for longer reaction times led to the conversion of 3 into 2a, suggesting 3 is an intermediate in the production of 2a.…”
Section: Borylation-reduction Of Phenyl-acetyl Derivativesmentioning
confidence: 99%
“…In 2005, Matthias Wagner’s team reported other N , N ′-chelate organoboron complexes in this reaction. They used dibromo(phenyl)borane, bromo(methyl)(phenyl)borane, bromo(ethoxy)(phenyl)borane to give bipyridine adducts with satisfactory yields ( 15 – 18 , 76–89%) [ 41 ], as shown in Scheme 4 . This reaction indicated that different N , N ′-chelate organoboron compounds could be obtained by adding distinct boron reagents under ambient temperature.…”
Section: Bipyridine-based Derivatives As Bidentate Ligandmentioning
confidence: 99%
“…The data presented in this study are openly available in references [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , …”
unclassified